Lights on the emergence backgrounds of the de facto autonomy of North and East Syria (NES). Its features of quasi state and interdependence with roots of the Kurdish question in Syria - Tillo, Khoushnaw (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research is presenting backgrounds to the sudden informal secession of the Kurdish regions in Syria from the central government of Damascus in 2012, to successively create a kind of de facto autonomy known as Autonomous Administration of North and East Syria (AANES).
Keywords: Kurdish question in Syria; AANES; Syrian crisis; Syrian civil war; indigenous session attempts; YPG; YPJ; International Coalition against ISIS; Jihadist groups; de facto autonomy in NES; quasi state